In situ anaerobic microbiological treatment of a chlorobenzene contaminated groundwater - Fehér Balázs; Csákvári Eszter; Komóczy Attila; Lendvai József; Zsilinszky Ingrid; 29th International Symposium on Analytical and Environmental Problems Szeged 2023. november 13-14. (University of Szeged Szeged, 2023)
A one-year site investigation was conducted in a contaminated area near a pharmaceutical industry. The main contaminants were chlorobenzene and benzene. Over time, concentration of the contaminants decreased below regulatory level under anaerobic conditions by biostimulation. To confirm the transformation processes and reveal the mechanisms, a corresponding laboratory microcosm study was set up which completed demonstrating the microbial degradation of these two main pollutants. Assumptions about the transformation processes inferred from field data were confirmed by microcosm studies, consequently necessary supplementary information were provided for bioremediation technologies.
Keywords: Természettudományok; Kémiai tudományok